Consumers' perceptions towards mobile halal application system - Abu Bakar, Elistina; Rosslee, Nashaqilla Norlee; Saidin, Aznan Zuhid (2014)
Due to the advancement in the communication system, all the information are easily available. This includes the mobile application system which can act as tracking and educational tools for Muslim consumers to validate JAKIM halal logo. The study was conducted in Gadek, Alor Gajah Malacca to gauge the perceptions of consumers towards these mobile application systems. The data was collected using questionnaires and was analysed using Statistical Package for Social Science (SPSS). A total of 150 respondents were selected by systematic sampling. The study demonstrates that the consumers do not put high trust towards the mobile application system. They also claimed that they did know and understand the current available systems. However, the consumers agree that these mobile applications can act as educational tools to inculcate awareness about halal products among Muslim. The inferential statistic also indicates that there is a significant relationship between the usage of mobile applications system and the purchasing of halal cosmetics (r = 0.279, p = 0.000). This study gives implication to JAKIM, HDC, KPDNKK and consumer associations to play a role in shaping the culture of buying halal products among consumers through mobile application system. Nevertheless, comprehensive awareness activities need to be done to ensure the success of this system.